Linear Sensing Response to Ethanol by Indium Oxide Nanoparticle Layers. (19th September 2013) - Singh, Vidya N.; Partheepan, Ganesan
Abstract : Indium oxide nanoparticles having well-defined particle sizes were synthesized using a chemical capping method. These nanoparticles were used for making the nanoparticle layers without altering the size and morphology of these particles. These nanoparticles and nanoparticle layers were characterized using XRD, TEM, HRTEM and AFM. The ethanol sensing behavior of the nanoparticle layers were studied at different ethanol concentrations. It was observed that the sensor response was linear to the ethanol concentration in the range of 10–1000 ppm. The ethanol sensing behavior has been explained on the basis of the creation of a depletion region due to the adsorbed oxygen and release of the electron in the conduction band in the presence of ethanol (as it takes away the adsorbed oxygen). The explanation has been supported by EDAX results.